How safe are NOACs compared with phenprocoumon after pulmonary vein isolation with the cryoballoon technique using purse-string suture closure?. (1st December 2017) - Akkaya, Ersan; Berkowitsch, Alexander; Zaltsberg, Sergej; Deubner, Nikolas; Greiss, Harald; Hain, Andreas; Hamm, Christian W.; Sperzel, Johannes; Kuniss, Malte; Neumann, Thomas
Abstract: Introduction: The aim of this observational study was to compare the postprocedural incidence of bleeding and thromboembolic complications associated with novel oral anticoagulants (NOACs) with that of interrupted and continuous phenprocoumon after pulmonary vein isolation (PVI) using a purse-string suture (PSS) closure of the puncture site. Methods and results: Consecutive patients who had undergone PVI via cryoballoon ablation were divided into the following groups: (1) interrupted phenprocoumon with heparin bridging ( n  = 101), (2) continuous phenprocoumon targeting an internationally normalized ratio > 2 ( n  = 70), and (3) NOACs without bridging that were restarted 2–4 h after the procedure ( n  = 185). Protamine was not administered after venous closure with PSS at the end of the procedure. The total complication rate was significantly lower in group 3 than in groups 1 and 2 (1.62% vs. 6.93% vs. 7.14%, p  = 0.04). The hospital costs were lower and the hospital stay length was significantly shorter (4484 ± 3742 vs. 6082 ± 4044 Euro vs. 4908 ± 2925, p  = 0.03; 1.94 ± 1.67 vs. 2.70 ± 1.80 vs. 2.19 ± 1.30 days, p  < 0.01). No thromboembolic event occurred. Vascular complications were the most common complications noted (80%). The occurrence of any complication led to a significantly longer hospital stay (5 vs. 2 days, p  < 0.01) and higher costs (10, 052 ± 6241 Euro vs. 4747 ± 3447, p  < 0.01). The vascular complication rate after PSS was independent of intraprocedural heparin dosage and activated clotting time. Conclusions: NOACs have a lower complication rate and appear to be safer in this setting than phenprocoumon. The hospital costs and hospital stay length after PVI was significantly reduced in patients treated with NOACs compared with phenprocoumon.